2015
DOI: 10.1080/17457300.2014.966120
|View full text |Cite
|
Sign up to set email alerts
|

Driving under the influence of alcohol in Cali, Colombia: prevalence and consumption patterns, 2013

Abstract: This study's goal was to establish the prevalence of driving under the influence of alcohol (DUI) and alcohol consumption patterns among drivers in Cali, Colombia, in 2013. A cross-sectional study based on a roadside survey using a stratified and multi-stage sampling design was developed. Thirty-two sites were chosen randomly for the selection of drivers who were then tested for blood alcohol concentration (BAC) and asked to participate in the survey. The prevalence of DUI was 0.88% (95% confidence intervals [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…RTIs were associated with weekends. This may be explained by the higher prevalence of driving under the in uence of alcohol on weekends in the city [24]. However, there was also a reduction in the proportion of RTI over time (Figure 1), which differs from a study in Sao Paulo, Brazil, which found an increase in the frequency of RTIs over time [25].…”
Section: Discussionmentioning
confidence: 61%
“…RTIs were associated with weekends. This may be explained by the higher prevalence of driving under the in uence of alcohol on weekends in the city [24]. However, there was also a reduction in the proportion of RTI over time (Figure 1), which differs from a study in Sao Paulo, Brazil, which found an increase in the frequency of RTIs over time [25].…”
Section: Discussionmentioning
confidence: 61%
“… 28 Honduras does not have regular inspections of roads, policies separating road users from pedestrians or other vulnerable road users, and have national road safety strategy. 29 Countries with similarities to Honduras has seen benefit in using cameras for detecting traffic violations, 30 enforcing drinking and driving laws, 31 separating physically vulnerable road users by creating motorcycle- and bicycle-exclusive lanes, 32 increasing pedestrian crossing signs and clearly marking crosswalks, 33 targeting motorcyclists or bicyclists not wearing helmets and designated vests, 34 and targeting pedestrians crossing at prohibited places. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, drunk driving may be a primary cause of road traffic collisions. Currently, investigations regarding drunk driving have been undertaken in most countries [20][21][22][23][24], and in general, alcohol breath testing is used first to determine if a driver is drunk, followed by testing blood alcohol concentration (BAC). BAC was used to decide drunk driving behavior.…”
mentioning
confidence: 99%